ESSAI DE LUTTE in vitroPAR LE GLYPHOSATE CONTRE DES CHAMPIGNONS TELLURIQUES PHYTOPATHOGENES : FUSARIUMET PYTHIUM (Sciences & Technologie. C, Biotechnologies, 2007)
Cryptogamic diseases are considered as limiting factors of cereals, crop and forest production, because causing considerable losses. These diseases are caused by several species. The most frequently blamed belong to Rhizoctonia, Fusariumand Pythium kinds. These two last genus appear to be sensitive to an organo-phosphorated weedkiller: the glyphosate [1, 2, 3]. The tests carried out towards Fusarium oxysporum, Fusarium oxysporum f. sp albedinis(Killian & Maire) Gordon, and some stocks of Pythium, show that glyphosate concentrations tested (0.5 - 1 - 1.5 and 2 mM) decrease Fusaria mycelian growth until inhibiting it at 2mM concentration level; whereas growth of Pythiumis inhibited from 0.5mM concentration. Microscopic studies of the mycelial colonies reveal that 0.5 - 1 and 1.5 mM glyphosate concentrations increase Fusarium oxysporumconidia number; 1.5 mM molarity stimulates chlamydospore formation. Concerning with Fusarium oxysporum f. sp albedinis however, a reduction in the number of conidia is observed at 0.5 mM; their absence at 1 and 1.5 mM is noted under the experimental conditions (T = 28°C, medium PDA). 2 mM concentration inhibits growing speed and reproductive organs production of Fusarium and Pythiumspecies.